1981
DOI: 10.1523/jneurosci.01-09-00956.1981
|View full text |Cite
|
Sign up to set email alerts
|

The visual claustrum of the cat. I. Structure and connections

Abstract: The cat's dorsocaudal claustrum was studied in Golgi preparations, by electron microscopy, and by anterograde and retrograde tracer techniques. It receives a convergent retinotopic projection from several visual cortical ares, including areas 17, 18, 19, 21a and PMLS (posteromedial lateral suprasylvian area). The projection arises from spiny dendrite cells (pyramidal and fusiform) in the middle of cortical layer VI. As shown by a double label experiment, they form a separate population from those projecting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
200
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(216 citation statements)
references
References 38 publications
15
200
1
Order By: Relevance
“…All layer 6 cells, for example, received direct excitation from geniculate afferents, and therefore so did all cortico-geniculate neurones. Layer 6 also contains cells projecting to the visual claustrum (LeVay & Sherk, 1981). Although these cells were not studied specifically in the present investigation, the uniform monosynaptic excitation of layer 6 cells indicates that they also receive direct excitation from the l.g.n.…”
Section: Connexion Of Efferent Neuronesmentioning
confidence: 81%
“…All layer 6 cells, for example, received direct excitation from geniculate afferents, and therefore so did all cortico-geniculate neurones. Layer 6 also contains cells projecting to the visual claustrum (LeVay & Sherk, 1981). Although these cells were not studied specifically in the present investigation, the uniform monosynaptic excitation of layer 6 cells indicates that they also receive direct excitation from the l.g.n.…”
Section: Connexion Of Efferent Neuronesmentioning
confidence: 81%
“…For example, afferents from pulvinar and extrastriate cortex do not end in layers 4A or 4C (Benevento et al, 1975;Ogren and Hendrickson, 1976;Spatz, 1977;Tigges et al, 1977;Rockland and Pandya, 1981). While the claustrum projects in a topographic fashion to geniculo-recipient laminae, there is no evidence for the precise laminar segregation that characterizes LGN inputs (Carey et al, 1980;LeVay and Sherk, 1981). And the numerous other small nuclei that have known projections to striate cortex (e.g., locus ceruleus, nucleus dorsalis raphe, etc.…”
Section: Discussionmentioning
confidence: 99%
“…To the contrary, many callosal projections have been shown to be heterotopic (Zeki, 1971;Hedreen and Yin, 1981;Segraves and Rosenquist, 1982), and it has even been demonstrated that there are reciprocal interhemispheric connections between cortical and subcortical structures such as the claustrum (LeVay and Sherk, 1981).…”
Section: Discussionmentioning
confidence: 99%